2020
DOI: 10.1007/s10120-020-01047-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of postoperative quality of life by PGSAS-45 following local gastrectomy based on the sentinel lymph node concept in early gastric cancer

Abstract: Background The usefulness of sentinel node navigation surgery (SNNS) for early gastric cancer has been demonstrated in a multicenter prospective study. However, quality of life (QOL) after local resection remains unclear. This present study investigated QOL after local resection and distal gastrectomy. Methods We examined 69 patients who underwent laparoscopic distal gastrectomy (LADG) (n = 44) and laparoscopic local resection (LLR) (n = 25) in our hospital between September 2011 and May 2018. We conducted a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 26 publications
1
30
0
Order By: Relevance
“…Few studies have assessed the QOL and nutritional status of patients following LR of the stomach with SNNS. According to an assessment using the PGSAS-45, patients who underwent CLEAN-NET with SNNS had better QOL than those who underwent laparoscopic distal gastrectomy (LDG) [ 79 ]. It was also reported that changes in body weight and the prognostic nutritional index were better in the LR group than in the LDG group [ 79 ].…”
Section: Sentinel Node Navigation Surgerymentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies have assessed the QOL and nutritional status of patients following LR of the stomach with SNNS. According to an assessment using the PGSAS-45, patients who underwent CLEAN-NET with SNNS had better QOL than those who underwent laparoscopic distal gastrectomy (LDG) [ 79 ]. It was also reported that changes in body weight and the prognostic nutritional index were better in the LR group than in the LDG group [ 79 ].…”
Section: Sentinel Node Navigation Surgerymentioning
confidence: 99%
“…According to an assessment using the PGSAS-45, patients who underwent CLEAN-NET with SNNS had better QOL than those who underwent laparoscopic distal gastrectomy (LDG) [ 79 ]. It was also reported that changes in body weight and the prognostic nutritional index were better in the LR group than in the LDG group [ 79 ]. As shown in Table 3 , the change in body weight after LR ranged from 96.2% to 97.4% [ 69 , 79 ].…”
Section: Sentinel Node Navigation Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…CLEAN-NET was beneficial since the stomach wall was not perforated with resection and achieved local resection. Combining local resection with SN biopsy, the post-gastrectomy symptoms were reported to be improved ( 44 ). Combining local resection using laparoscopy and endoscopic submucosal dissection, non-exposed endoscopic wall-inversion surgery (NEWS) was developed by Goto et al ( 45 ).…”
Section: Navigation Surgery Based On Sn Biopsy For Early Gastric Cancer: History and Current Statusmentioning
confidence: 99%
“… 8 , 9 Previous studies demonstrated the effectiveness of the sentinel node concept in the treatment of EGC. 6 , 10 , 11 The prognosis of EGC is mainly associated with lymph node metastases (LNM) and remnant cancer. The presence of positive resected margins, specifically positive vertical margins, during histology is significantly correlated with remnant cancer.…”
mentioning
confidence: 99%